2022
DOI: 10.1128/spectrum.00689-22
|View full text |Cite
|
Sign up to set email alerts
|

Effects of l -Serine on Macrolide Resistance in Streptococcus suis

Abstract: The emergence of antimicrobial resistance is a global challenge. However, new drug development efforts consume considerable resources and time, and alleviating the pressure on existing drugs is the focus of our work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…In veterinary medicine, macrolides and lincosamides can be used as feed and injection preparations for treating swine respiratory tract infections ( 14 , 36 ). In addition, tetracycline, florfenicol, and penicillins are frequently applied separately or in combination for treating S. suis infections ( 37 39 ). Notably, we found linezolid and vancomycin resistance (LVR), and these are last-resort antimicrobial agents for the treatment of multidrug-resistant Gram-positive bacterial infections, which poses a severe threat to public health.…”
Section: Discussionmentioning
confidence: 99%
“…In veterinary medicine, macrolides and lincosamides can be used as feed and injection preparations for treating swine respiratory tract infections ( 14 , 36 ). In addition, tetracycline, florfenicol, and penicillins are frequently applied separately or in combination for treating S. suis infections ( 37 39 ). Notably, we found linezolid and vancomycin resistance (LVR), and these are last-resort antimicrobial agents for the treatment of multidrug-resistant Gram-positive bacterial infections, which poses a severe threat to public health.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of disulfide bridges was also dispensable in certain antimicrobial peptides and the reduction in disulfide bonds increased the antimicrobial activity [34][35][36][37][38]. The addition of serine in combination with some antibacterial drugs enhanced the antimicrobial activity [39][40][41]. We also investigated the role of tryptophans in the studied peptide, as they may be necessary for the interaction of AMPs with bacterial membranes [42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…In view of this, increasing ROS production by regulating metabolic networks may enhance antibiotic activity [106]. Recently, Wu et al [110] found that L-serine is an ROS enhancer that can produce synergistic killing effects against macrolide-resistant Streptococcus suis in vitro and in vivo when combined with macrolide antibiotics. Further studies found that L-serine inhibited the production of intracellular H 2 S, reduced the production of Fe-S clusters, and restored the intracellular Fenton reaction, which, eventually, caused an increase in the level of bacterial endogenous reactive oxygen species, leading to intracellular DNA damage and bacterial death.…”
Section: Activation Of the Bacterial Metabolic Statementioning
confidence: 99%